Analysis of ginseng rusty root symptoms transcriptome and its pathogenesis directed by reactive oxygen species theory - Pengcheng Yu; Xiaowen Song; Wei Zhang; Yao Yao; Junling Ren; Liyang Wang; Wenfei Liu; Zhaoping Meng; Xiangcai Meng (Plant Direct)
Abstract Ginseng rusty root symptoms (GRS) is a primary disease of ginseng, which seriously decreases the yield and quality of ginseng and causes enormous losses to ginseng production. GRS prevention and control is still challenging due to its unclear etiology. In this study, the phloem tissue of healthy Panax ginseng (AG), the nonred tissue of the phloem epidermis around the lesion (BG), and the red lesion site tissue of GRS (CG) were extracted for mRNA transcriptomic analysis; 35,958 differentially expressed genes (DEGs) were identified and were associated with multiple stress resistance pathways, reactive oxygen species (ROS), and iron ion binding. Further study showed that the contents of O2•‐, H2O2, and malondialdehyde (MDA) were significantly increased in BG and CG tissues. Under anaerobic conditions caused by excessive soil moisture, the overproduction of ROS destroys cell membranes, simultaneously converting Fe2+ to Fe3+ and depositing it in the cell wall, which results in GRS, as evidenced by the success of the GRS induction test.